A new theoretical model of low cycle fatigue life for coiled tubing under coupling load. (June 2021) - Shaohu, Liu; Hao, Zhou; Hui, Xiao; Quanquan, Gan
Highlights: The theoretical model of low-cycle fatigue life is established based on plastic strain. The theoretical model feasibility is verified by the experimental result and FE value. The bending radius, the CT' OD and the internal pressure are the sensitive parameters. Abstract: Coiled tubing (CT) technology is widely used in oil and gas industry. In the operation process, low cycle fatigue failure is easy to occur. Therefore it is necessary to predict the fatigue life of CT. In this paper, a new theoretical model of low cycle fatigue life for CT is established, the feasibility of the theoretical model is verified by experimental result and Finite Element (FE) value. This method effectively solves the problem that the result of the previous model is not more accurate at some conditions. Using the theoretical model, the effect of CT steel grade, wall thickness, outer diameter (OD), reel radius, guider radius and internal pressure on the fatigue life are studied by using the theoretical model. The result shows that the reel radius, CT OD and internal pressure are the sensitive parameters that affect the fatigue life of CT.